2007
DOI: 10.1093/bja/ael282
|View full text |Cite
|
Sign up to set email alerts
|

Predicting postoperative nausea and vomiting with the application of an artificial neural network

Abstract: The ANN provided the best predictive performance among all tested models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 18 publications
2
10
0
2
Order By: Relevance
“…The AUC for the final model was 0.734, which exceeds the commonly recognized threshold of 0.70 to be considered diagnostically useful 39 and compares favorably with commonly cited risk-scoring models [30][31][32][33][34][35][36] designed to predict PONV (range for AUCs: 0.61-0.70). In addition to having acceptable utility for predicting ORADEs, it is important for a risk score to be practicable in the clinical setting.…”
Section: Incidence Of Orade Overall and By Gendersupporting
confidence: 49%
See 1 more Smart Citation
“…The AUC for the final model was 0.734, which exceeds the commonly recognized threshold of 0.70 to be considered diagnostically useful 39 and compares favorably with commonly cited risk-scoring models [30][31][32][33][34][35][36] designed to predict PONV (range for AUCs: 0.61-0.70). In addition to having acceptable utility for predicting ORADEs, it is important for a risk score to be practicable in the clinical setting.…”
Section: Incidence Of Orade Overall and By Gendersupporting
confidence: 49%
“…[27][28][29] For example, Kooij et al (2008) found that including a simple risk-scoring system designed to identify patients with a high risk of experiencing postoperative nausea and vomiting (PONV) as part of the routine preoperative screening process significantly improved guideline adherence for prescribing PONV prophylaxis. 27 Several risk-scoring models, mainly for PONV, 11,[30][31][32][33][34][35][36][37] based on a patient's clinical/demographic profile have been developed with the goal of aiding health care providers in identifying high-risk patients and providing an opportunity to determine the safest and most effective pain management strategy. While evaluation of these models has focused primarily on their utility for predicting ADEs, very few have also considered whether the risk scores can transitively predict downstream outcomes such as increased costs and length of stay (LOS).…”
Section: Study Design and Sample Selectionmentioning
confidence: 99%
“…In recent years ANN has been widely applied in computer-aided diagnosis [7, 8], outcome prediction [9, 10], and signal processing [11, 12]. A good predictive model for postoperative nausea and vomiting (PONV) helps us do risk classification and management.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies indicated that there was no linear correlation between MS and HRV [7,8]. Yet, other studies suggested that the relationship between HRV and sympathovagal activities could be influenced by subjects' active adjustments [9,10].…”
Section: Introductionmentioning
confidence: 99%